Genotypic correlates of susceptibility to HIV-1 attachment inhibitor BMS-626529, the active agent of the prodrug BMS-663068 - Zhou, N.; Nowicka-Sans, B.; McAuliffe, B.; Ray, N.; Eggers, B.; Fang, H.; Fan, L.; Healy, M.; Langley, D. R.; Hwang, C.; Lataillade, M.; Hanna, G. J.; et al. (Journal of antimicrobial chemotherapy, 2014)
In an 8 day monotherapy study of subjects infected with HIV-1 (subtype B) (NCT01009814), BMS-626529 (an attachment inhibitor that binds to HIV-1 envelope glycoprotein gp120), administered as the prodrug BMS-663068, produced substantial declines in plasma HIV-1 RNA. However, large variability in susceptibility to BMS-626529 was noted and virus with low susceptibility was less likely to be suppressed by BMS-663068 administration. The current analysis sought to investigate the genotypic correlates of susceptibility to BMS-626529. In vitro selection experiments, evaluation of clinical samples of subtype B from the monotherapy study and evaluation of intrinsically resistant subtype AE viruses were conducted. Reverse genetics was used to identify key substitutions in envelope clones responsible for reduced susceptibility. An M426L or S375M change were the major substitutions associated with reductions in susceptibility to BMS-626529 in baseline samples of subtype B viruses from the monotherapy study, with M434I and M475I contributing to a lesser extent. Class resistance in subtype AE viruses was mapped to 375H and 475I substitutions, found in the vast majority of these viruses. Analysis of multiple envelope clones from infected subjects showed higher intrasubject variability in susceptibility to BMS-626529 compared with other classes of entry inhibitors. These data define key genotypic substitutions in HIV-1 gp120 that could confer phenotypic resistance to BMS-626529.